2022
DOI: 10.1186/s10194-022-01451-7
|View full text |Cite
|
Sign up to set email alerts
|

Interictal osmophobia is associated with longer migraine disease duration

Abstract: Background Sensitization to sensory stimuli is an essential feature of migraine attacks. The relationship between the clinical course of migraine and increased sensitivity to olfactory stimuli has been little studied so far. Methods We analyzed the frequency and quality of osmophobia depending on the phase of migraine in patients with episodic and chronic migraine treated in an tertiary headache center with regard to gender, age, medical history an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…While severe and pulsating headaches are the hallmark of migraine, an important overlooked feature of the disorder is the presence of osmophobia 7–9. Up to 95% of all migraineurs seem to be affected by osmophobia during and between migraine attacks 10–13. Odours are known to trigger and aggravate migraine attacks and migraineurs often display altered odour threshold and hypersensitivity to odours 13–15.…”
Section: Introductionmentioning
confidence: 99%
“…While severe and pulsating headaches are the hallmark of migraine, an important overlooked feature of the disorder is the presence of osmophobia 7–9. Up to 95% of all migraineurs seem to be affected by osmophobia during and between migraine attacks 10–13. Odours are known to trigger and aggravate migraine attacks and migraineurs often display altered odour threshold and hypersensitivity to odours 13–15.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, according to the results of a real-world study, the presence of cutaneous allodynia could be a predictor of responsiveness to erenumab (32). In 113 migraineurs, 38.1% had preictal olfactory hypersensitivity, which is associated with longer duration of illness and migraine-related burden, suggesting that osmophobia may be associated with increasing central sensitization in the progression of migraine (33). Taken together, the presence of osmophobia in our study may be an important non-headache symptom predictive of response to CGRP mAb treatment, possibly reflecting the involvement of the CGRP pathway and central sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that patients with migraine had enhanced cortical responsiveness to visual cues during the interictal period. Other studies found that patients with migraine may have interictal osmophobia, and that higher olfactory sensitization may be associated with a higher burden of disease ( 18 , 19 ). Patients with episodic or chronic migraine may also have enhanced levels of cortical excitability during the interictal phase compared to normal control subjects that contributes to sensory hypersensitivities ( 77 , 78 ), as well as interictal autonomic abnormalities ( 22 ).…”
Section: Non-emotional (“Neurological”) Symptoms: Physiologic and Neu...mentioning
confidence: 99%
“…In addition to the headache phase, migraine can be accompanied by a constellation of other manifestations in varying combinations apart from the symptomatology listed in the diagnostic criteria, including visual disturbances, osmophobia, allodynia (i.e., as the normally non-noxious stimulus from light touch or brushing of the skin causing pain or discomfort), pain on movement, motion sickness, vestibular dysfunctions, cognitive symptoms, and cranial autonomic symptoms (Figure 1). Patients with migraine may experience many of these symptoms even in the interictal phase, although generally at a reduced frequency and/or intensity (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%